Predicting Switching Intention Among Generation Y Using DeLone & McLean (Study on Shopee App) - Made Pradnyan Permana Usadi; Putu Wahyu Dwinata JS; I Putu Oka Permadi (Faculty of Economics and Business, Universitas Malikussaleh, 2022)
The objective of this study is to look at the impact of systemquality, information quality, and service quality on satisfaction and switchingintention among Generation Y Shopee users. Data analyzed using PartialLeast Square. The result shows that system quality, information quality, andservice quality significantly has a positive impact on satisfaction. At thatpoint satifaction was moreover found to have a negative impact on intentionto switch. Service quality was found to have a more prominent impact. Thisimplies that Shopee needs to focus on improving service quality, since serviceis considered to have an important part in determining user satisfaction.